Leyla loop: a time-saving suture technique for robotic atrial closure - Kilic, Leyla; Senay, Sahin; Gullu, A. Umit; Alhan, Cem (OXFORD UNIV PRESS, 2013)
The longer durations of cardiopulmonary bypass and aortic cross-clamp times remain the disadvantages of robotic or minimally invasive cardiac surgery. For this reason, every small contribution to speeding up these procedures is of the utmost importance. Here, we present a practical, easy and time-saving suture technique for atrial closure. It consists of a hand-made loop at one end of the suture and saves the time otherwise consumed by knotting. It may also be used during conventional or minimally invasive cardiac surgery.
Keywords: Robotics surgery; Minimally invasive surgery; Atrium